2014
DOI: 10.1097/md.0000000000000115
|View full text |Cite
|
Sign up to set email alerts
|

Multiparametric Evaluation of Breast Lesions Using PET-MRI

Abstract: The purpose of this study was to evaluate the diagnostic accuracy of multiparametric evaluation of breast lesions combining information of dynamic contrast-enhanced magnetic resonance imaging (DCE-MRI), diffusion-weighted imaging (DWI), and 18F-fluoro-deoxi-glucose (18F-FDG) positron emission tomography/computed tomography (PET-CT). After approval of the institutional research ethics committee, 31 patients with suspicious breast lesions on MRI performed 18F-FDG PET-CT with a specific protocol for breast evalua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
10
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 26 publications
3
10
0
Order By: Relevance
“…A lesion had to meet one of three criteria: a washout curve on DCE MRI, ADC min <1.00 × 10 mm/s, or 18 F‐FDG uptake above background. The specificity in this study was 55% . In another multiparametric study, Pinker et al included four parameters: PET, DCE MRI, DWI, and 1hydrogen‐MRS, in their evaluation of 78 indeterminate or suspicious breast lesions .…”
Section: Index Lesion Evaluationmentioning
confidence: 64%
See 2 more Smart Citations
“…A lesion had to meet one of three criteria: a washout curve on DCE MRI, ADC min <1.00 × 10 mm/s, or 18 F‐FDG uptake above background. The specificity in this study was 55% . In another multiparametric study, Pinker et al included four parameters: PET, DCE MRI, DWI, and 1hydrogen‐MRS, in their evaluation of 78 indeterminate or suspicious breast lesions .…”
Section: Index Lesion Evaluationmentioning
confidence: 64%
“…DCE breast MRI has a high sensitivity, reported at up to 100%, and a positive predictive value above 35% . PET/CT is not routinely performed for breast cancer detection because is it not adequately sensitive, especially for lobular cancers and for cancers less than 1 cm . Authors have investigated whether combining DCE MRI and PET data in the breast can improve the diagnostic accuracy for breast cancer, but have found that the addition of PET often decreases the sensitivity of DCE‐MRI.…”
Section: Index Lesion Evaluationmentioning
confidence: 99%
See 1 more Smart Citation
“…Differences in patient positioning during PET/CT and MRI examinations may alter the quantitative results of these imaging modalities. Whole body PET/MRI not only facilitates quantitative tumor characterization, it also allows for confident detection of primary breast cancer, satellite lesions, and distant metastases while at the same time decreasing radiation dose to the patient compared to PET/CT [4143]. When PET/MR was performed after PET/CT with a single injection, there were strong correlations between SUV values from PET/CT and PET/MRI in breast cancer metastases [44].…”
Section: Discussionmentioning
confidence: 99%
“… 2 Currently, breast tumor vascularity can be assessed by noncontrast-enhanced ultrasonography, such as color Doppler flow imaging (CDFI), and contrast-enhanced imaging techniques, such as dynamic contrast-enhanced magnetic resonance imaging (DCE-MRI), contrast-enhanced ultrasound (CEUS), and dynamic contrast-enhanced computed tomography. 3 5 CDFI can provide information on tumor vascularity associated with breast malignancy; however, it has been proven to be unreliable in differentiating benign from malignant breast lesions when compared with the invasive imaging modalities listed above. 6 , 7 The number of vessels seen with CDFI often indicates the macrovascularity of breast cancers, but not the microvasculature.…”
Section: Introductionmentioning
confidence: 99%